The Roma Holocaust/Roma Genocide in Southeastern Europe: Between Oblivion, Acknowledgment, and Distortion (New York; Boston: The Auschwitz Institute for the Prevention of Genocide and Mass Atrocities; The François-Xavier Bagnoud Center for Health and Human Rights at Harvard University, 2022.), 147 str. (Časopis za suvremenu povijest, 2022)
Prikaz knjige